Attitude of Academicians towards Increased Retirement Age (Indian Journal of Extension Education, 2012)
Initially a set of ninety statements was prepared to construct the attitude scale with the help of available literature, discussion with subject matter specialists and extension scientists. The editing of statements was done with informal criteria and eighty three (83) unambiguous generalized relevant attitude statements towards increased retirement age of college teachers and scientists were selected for developing the attitude scale. The method of equal-appearing intervals as described by Thurstone and Chave (1929) was used for construction of the attitude scale. All the selected statements were rented through a group of fifty (50) judges for their responses towards each statement on eleven-point continuum varying from extremely unfavourable to extremely favourable. Thirty (30) judges returned the statements with their responses. The final selection of the statements constituting the attitude scale was completed with the help of scale value and Q values of all the 83 statements. 24 statements having Q value three and less than three were selected for the final scale to measure attitude towards increased retirement age of academicians. 100 randomly selected male as well as female academicians (college teachers and scientists) from different universities and institutions were taken as respondents to study the attitude towards increased retirement age. It was found that majority of the old age male and female academicians possessing M.Phil./Ph.D. degree with long service experience has favourable attitude towards increased retirement age while it was also inferred that the young male teachers favoured while female teachers favoured the increased retirement age of college teachers and scientists.